BRCA1 gene expression in relation to prognostic parameters of breast cancer - Manal Kamal; Yasser H. Shaaban; Mohamed Shehata; Amr T. El-Kashif; Emmad E. Habib; Khadiga Abu Gabal; Samia El-Naggar (Frontiers Media S.A., 2011)
The tumor suppressor gene, BRCA1 has been conferred to increase the susceptibility to breast cancer in younger women. This work studied the expression of BRCA1 (mRNA) in women with breast cancer in relation to other prognostic parameters such as histological type and grade of cancer, hormone receptor status, human epidermal growth factor receptor 2 (HER2/neu) and CA15-3. Thirty patients with positive family history of breast cancer and a control group of 20 healthy subjects were also included for the study. Ribonucleic acid (RNA) extraction from breast cancer tissues was done (considered suitable for RNA extraction if 70% or more of the tissue section contained tumor) and was followed by real-time reverse transcription polymerase chain reaction. BRCA1 expression was assessed and correlated with age, histological type and grade of breast cancer, estrogen and progesterone receptor (ER, PR) status, HER2/neu expression and CA15-3 levels. The mean age of patients was 54.8 ± 10.49 years. Of the 30 breast cancer cases studied, the majority (77%) was of high histological grade and the most common histological type was infiltrating ductal carcinoma (20 cases). ER expression was positive in 53.3% of breast cancers, while PR expression was positive in 50% of cancers. BRCA1 mRNA was found in 6 patient samples (20% of the breast cancer patients) while the remaining 24 patients (80%) showed negative BRCA1 mRNA expression as well as the control group. A positive significant relationship was demonstrated between BRCA1 (mRNA) expression and high histological grade, negative estrogen and progesterone receptor status, and high levels of serum CA15-3. A significant negative correlation was found between BRCA1 mRNA expression and age (r = −0.683; p < 0.01). The study demonstrated lack of BRCA1 gene expression (mRNA) in the majority of breast cancer cases and confirmed the relationship between BRCA1 expression and parameters that determine poor prognosis in breast cancer. The results suggested that BRCA1 is seen in high-risk women known with positive family history of breast cancer.